2007
DOI: 10.1557/proc-1063-oo06-01
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Porous Silicon in a Simulated Gastrointestinal Tract: Modeling the Biocompatibility of a Monolayer Protected Nanostructured Material

Abstract: Owing to its photoluminescent properties and high surface area, porous silicon (por-Si) has shown great potential toward a myriad of applications including optoelectronics, chemical sensors, biocomposite materials, and medical implants. However, the native hydride-termination is only metastable with respect to surface oxidation under ambient conditions. Por-Si samples oxidize and degrade even more quickly when exposed to saline aqueous environments. Borrowing from solution phase synthetic methods, a selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It was shown that bare pSi exhibited high surface oxidation after eighteen hours incubation in simulated intestinal fluid. [186] After functionalization with alkyl groups, Albrecht et al demonstrated that the porous particles had high resistance to oxidation in the gastric and intestinal fluids. [186] Surface oxidation and other chemical/physical exchanges between the particle and GI environment can produce unpredictable toxicity by reactive oxygen species (ROS).…”
Section: Biocompatibility Assessment For Si and Sio Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that bare pSi exhibited high surface oxidation after eighteen hours incubation in simulated intestinal fluid. [186] After functionalization with alkyl groups, Albrecht et al demonstrated that the porous particles had high resistance to oxidation in the gastric and intestinal fluids. [186] Surface oxidation and other chemical/physical exchanges between the particle and GI environment can produce unpredictable toxicity by reactive oxygen species (ROS).…”
Section: Biocompatibility Assessment For Si and Sio Particlesmentioning
confidence: 99%
“…[186] After functionalization with alkyl groups, Albrecht et al demonstrated that the porous particles had high resistance to oxidation in the gastric and intestinal fluids. [186] Surface oxidation and other chemical/physical exchanges between the particle and GI environment can produce unpredictable toxicity by reactive oxygen species (ROS). However, if the particles are already oxidized, the contribution of these processes can become negligible.…”
Section: Biocompatibility Assessment For Si and Sio Particlesmentioning
confidence: 99%